2016
DOI: 10.1158/1078-0432.ccr-16-0205
|View full text |Cite
|
Sign up to set email alerts
|

Analytic Validation of RNA In Situ Hybridization (RISH) for AR and AR-V7 Expression in Human Prostate Cancer

Abstract: Purpose RNA expression of androgen receptor splice variants may be a biomarker of resistance to novel androgen deprivation therapies in castrate resistant prostate cancer (CRPC). We analytically validated an RNA in situ hybridization (RISH) assay for total AR and AR-V7 for use in formalin fixed paraffin embedded (FFPE) prostate tumors. Experimental Design We used prostate cell lines and xenografts to validate chromogenic RISH to detect RNA containing AR exon 1 (AR-E1, surrogate for total AR RNA species) and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 48 publications
1
26
0
1
Order By: Relevance
“…Among these, AR-V7 is the best-characterized due to frequent detection of the AR exon 3/CE3 splice junction by RNA-seq and RT-PCR (12, 13, 1517), high expression of exon CE3 measured by RNA-ISH (20, 25, 43), and availability of AR-V7-specific antibodies to interrogate protein expression in tissues (19, 44, 45). In this study, we found that AR-V9 is frequently co-expressed with AR-V7 in CRPC cell lines, PDX tissue, circulating tumor cells, and biopsies of metastatic CRPC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these, AR-V7 is the best-characterized due to frequent detection of the AR exon 3/CE3 splice junction by RNA-seq and RT-PCR (12, 13, 1517), high expression of exon CE3 measured by RNA-ISH (20, 25, 43), and availability of AR-V7-specific antibodies to interrogate protein expression in tissues (19, 44, 45). In this study, we found that AR-V9 is frequently co-expressed with AR-V7 in CRPC cell lines, PDX tissue, circulating tumor cells, and biopsies of metastatic CRPC.…”
Section: Discussionmentioning
confidence: 99%
“…For example, signals from RNA-ISH assays with probes complementary to AR exon CE3 have been utilized to assess AR-V7 mRNA levels in prostate cancer tissues (20, 25, 43). Our data indicate these RNA-ISH signals would represent a composite of AR-V7 and/or AR-V9.…”
Section: Discussionmentioning
confidence: 99%
“…An average of 67 mm 2 of tumor tissue area was selected for analysis (range: 16–152 mm 2 ). CD8+ or CD3+ cells within the selected tumor area were identified by Aperio software as previously described (42), and the ratio of CD8+ or CD3+ cells to the total tumor area analyzed was calculated for each case. PD-L1 staining was scored as positive if >1% of immune cells or tumor cells showed PD-L1 membranous positivity.…”
Section: Methodsmentioning
confidence: 99%
“…However, limitations and discrepancies of the studies about the predictive value of AR-V7 mRNA in CTCs due to AR-V7 expression in non-malignant cells (e.g., hematopoietic cells, peritumoural tissue, benign glands) have already been reported [28][29][30].…”
Section: Discussionmentioning
confidence: 99%